FAKTOR – FAKTOR PRODUKSI YANG BERPENGARUH TERHADAP PENDAPATAN USAHA TANI UBI KAYU ( Manihot utilissima) DI DESA ALASSUMUR KECAMATAN PUJER KABUPATEN BONDOWOSO - Hasani; Mulyono, Idi (FORAGRI : Jurnal Ilmu Pertanian, 2022)
The purpose of this study is to determine the effect of seed costs on farmers’ income, the effect of labor costs on and the effect of fertilizer costs on farmers’ income in cassava farming. The method used is linear regression to determine the cost of seeds, labor and fertilizer for the income of cassava farmers. From the results of the analysis of seed costs on farmers’ income, the coefficient -1,323 shows that seed costs have a significant effect on income in income. From the results of fertilizer cost analysis in farmers’ income, the coefficient of 1,997 with a significance level of 0.000 is smaller than <0.05, it can be concluded that the variable fertilizer costs have a significant effect on income in cassava agriculture. From the results of the analysis of labor costs in the farmers’ income obtained by the coefficient of 0.259 with a significance level of 0.617 greater than> 0.05, it can be concluded that the cost of variable labor has no significant effect on income in cassava agriculture. The cost factor of seeds and labor has a negative effect on the income of cassava farmers, while the fertilizer factor has a positive effect on the income of cassava farmers.